Illegitimate Tasks as an Impediment to Job Satisfaction and Intrinsic Motivation: Moderated Mediation Effects of Gender and Effort-Reward Imbalance - Omansky, Rachel; Eatough, Erin M.; Fila, Marcus J. (Frontiers in Psychology, 2016)
The current work examines a contemporary workplace stressor that has only recently been introduced into the literature: illegitimate tasks. Illegitimate tasks are work tasks that violate identity role norms about what can reasonably be expected from an employee in a given position. Although illegitimate tasks have been linked to employee well-being in past work, we know little about the potential explanatory mechanisms linking illegitimate tasks to work-relevant negative psychological states. Using a sample of 213 US-based employees of mixed occupations and a cross-sectional design, the present study examines job satisfaction and intrinsic motivation as outcomes of illegitimate tasks. Additionally, we examine perception of effort-reward imbalance as a potential mediating mechanism through which illegitimate tasks relate to job satisfaction and intrinsic motivation, highlighting a possible pathway by which these relationships are functioning. Finally, we explore gender as a socially constructed variable that could contribute to variation in responses to illegitimate tasks and moderate the mediated link between illegitimate tasks and outcomes. Results indicated that illegitimate tasks were significantly related to job satisfaction and intrinsic motivation both directly and indirectly through perceptions of effort-reward imbalance in the predicted directions. Moreover, a moderated-mediation effect was found such that male workers reacted more than female workers to illegitimate tasks through the mechanism of perceived effort-reward imbalance.